Marketing Research Project to Study the Attitudes and Preferences of Travelers Towards an Innovative Mode of Transport in Poland - Ewa PRYMON-RYS (Communications of International Proceedings, 2023)
The article presents the assumptions and process of marketing research conducted by the Hyperloop Consortium as part of a project to assess the social, legal, economic and technological possibilities and limitations of implementing vacuum rail technology in Poland. Vacuum rail is perceived as a very innovative, future-oriented, energy- and time-saving transport solution, which is being researched in many countries. The growing number of scientific publications on Hyperloop demonstrates the importance of research on the concept, although most of them focus on technical and design aspects. The research described in this article is a pioneering study that combined an evaluation of social acceptance of the concept, passenger attitudes, concerns and perceived risks, and their experience of simulated Hyperloop ride. The quantitative and qualitative research was followed by experiments using a virtual reality-based transport module simulator. The experimental procedure included: video presentation, a few-minute VR ride accompanied by psycho-physiological measurements and a questionnaire survey. The next phase of the research procedure (with corresponding stages) included tests using a mechanical simulator of the vacuum rail passenger module. The results of the survey verified the initial assumptions of the project and provided important information on the conditions of vacuum rail travel, the equipment of the passenger modules, the accepted price level and the solutions expected or suggested by the passengers. The positive reception of vacuum rail technology by potential Hyperloop passengers indicates a very positive attitude towards this innovative mode of transport and optimistic assumptions about the possibility of implementing this solution in Poland.
Keywords: ethical leadership; psychological capital; organizational citizenship behavior